Systematics of the Rhinella margaritifera complex (Anura, Bufonidae) from western Ecuador and Panama with insights in the biogeography of Rhinella alata - dos Santos, Sueny P.; dos Santos, Sueny P.; S. R. Ron; S. R. Ron (Zookeys, 2015)
The Rhinella margaritifera species group consists of 17 species of toads distributed in tropical and subtropi- cal South America and eastern Central America. The identity of some of its species is poorly understood and there are numerous undescribed cryptic species. Among them, the status of Rhinella margaritifera is one of the most problematic. Its range includes lowland rainforests separated by the Andes, the Chocoan rainforest to the west and the Amazonian rainforest to the east. This distribution is puzzling because the Andes are an old and formidable barrier to gene flow and therefore should generate vicariant speciation be- tween disjunct lowland populations. Herein we clarify the taxonomy of populations of the R. margaritifera complex from Central America and the Chocó region of South America. The morphological and genetic variation of R. margaritifera was examined from 39 populations from Chocó, 24 from the upper Amazon region of Ecuador, and 37 from Panama, including the holotype of the Panamanian R. alata. Phylogenetic analyses were performed based on mitochondrial genes 12S rRNA, 16S rRNA, and cytochrome c oxidase I (COI) and the nuclear gene Tyrosinase (Tyr). The genetic and morphological data show that Panamanian and Chocoan populations are conspecific. In the phylogeny, populations from Chocó and Panama form a well-supported clade. The morphology of the holotype of R. alata falls within the variation range of Panamanian and Chocoan populations. Based on all this evidence, we assign the populations from western Ecuador and Panama to R. alata and demonstrate that the unusual distribution pattern of “R. margaritif- era” on both sides of the Andes was an artifact of incorrectly defined species boundaries.
Centro Jambatu - ID 1560